AN ANALYSIS OF INTONATION PATTERN IN THE PRE SERVICE ENGLISH TEACHER TALKS - Desinta Ika A; Elysa Hartati; Rahmaditya KARW (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2022)
This study examined the intonation pattern errors occurring in pre-service English teachers talks and investigated the causes of the errors. This research used three instruments to gain the data: documentation, observation and interview. Then, the collected data were analyzed using Roach, Wells Haycraft  theories and PRAAT software analysis. The participants of this study were 8th semester students in English Language Education Study Program at one of the private universities in Yogyakarta. Three recordings of pre-service English teachers talks were transcribed by unitizing schemes, sampling plans, recording/coding, reducing data, abductively inferring contextual phenomena, and narrating the result information of the data collected. The results showed that two kinds of intonation patterns occurred in pre-service English teachers, falling and rising. The dominant error of speaker was final rising in WH-question sentence type. The errors were caused by the physical impediment, inability in manipulating the pitch voice, and inability to keep the level tone stable. In addition, it was also due to the pre-service English teachers L1 mother tongue. This study gave information of pre-service English teacher ability, obstacle, and the causes of errors in producing intonation tone. It can be a reference for pre-service English teachers to look for pre-service teacher ability in mastering pronunciation especially intonation.